Psychometric properties of the brief version of the Driving Anger Scale (DAS) in Spanish language: Differences by age, gender and traffic violations. - Egea-Caparrós, Damián Amaro; Velandrino Nicolás, Antonio Pablo; Fernández-Ros, Encarna; Prieto-Martínez, Iván (Anales de Psicología / Annals of Psychology, 2012)
The personality factors are an important group of factors associated to traffic accidents. Specifically, driving anger can be one of the more remarkable variables because it can motivate and elicit aggressive behavior. To measure this personality factor Deffenbacher, Oetting & Lynch (1994) developed the Driving Anger Scale (DAS) and its abbreviated version (with only 14 items). Because of the widely dissemination of this short version, owing to its validity and time-saving properties, it have been accomplished its adaptation into Spanish too (Herrero-Fernández, 2011). This first Spanish adaptation did not use general population and found a three-factorial structure. In the present study we have carried out an extension to general population, including data on traffic violations. Appropriate psychometric properties and a new four-factorial structure of «driving anger» have been achieved. The three factors on previous short versions of the DAS have been called «traffic obstructions», «illegal driving», and «hostile gestures», but we have find a fourth factor we have named «possibility of being fined». Its rationale is both empirically and theoretically discussed.